RESEARCH ON FORMULATION AND EVALUATION OF INSITU MUCOADHESIVE NASAL GELS OF METOCLOPRAMIDE HYDROCHLORIDE - Gandhi, Parth; Rathod, Hemant; Patel, Saurabh; Gandhi, Ronak; Khinchi, M. P.; Agrawal, Dilip; Kabra, Mahavir (Asian Journal of Pharmaceutical Research and Development, 2014)
The prolonged residence of drug formulation in the nasal cavity is of utmost importance for intranasal drug delivery. The objective of the present investigation was to develop a mucoadhesive in situ gel with reduced nasal mucocilliary clearance in order to improve the bioavailability of the antiemetic drug, Metoclopramide Hydrochloride. The in situ gelation upon contact with nasal mucosa was conferred via the use of the thermogelling Methyl cellulose whereas mucoadhesion and drug release enhancement were modulated via the use of sodium alginate and polyethylene glycol polymers respectively. The results revealed that the mucoadhesive polymer increased the gel viscosity but reduced its sol gel transition temperatures and the drug release. The inclusion of polyethylene glycol polymer counteracted the effect of mucoadhesive polymer where by it decreased the gel consistency and increased the sol gel transition as well as in vitro drug diffusion. The in vitro tests performed for mucoadhesive strength and drug diffusion showed that nasal in situ gelling formulations prepared are having good mucoadhesive strength with nearly100% drug diffusion within four hours. So this study points to the potential of mucoadhesive in situ nasal gel in terms of ease of administration, accuracy of dosing, prolonged nasal residence and improved nasal bioavailability.